ANALISIS POTENSI WISATA AMANAH BORNEO PARK BANJARABARU SEBAGAI DESTINASI EKOWISATA BERKELANJUTAN DI KALIMANTAN SELATAN - Listi Purnamma; Putri Romaulina Siregar; Windy Utami Putri; Fendy Hariatama H; Oga, Holga; Clarasinta Munika; Adindha Ekasari S.R.P (FKIP Unswagati, 2025)
Amanah Borneo Park in Banjarbaru, South Kalimantan, is one of the natural tourist destinations with the potential to be developed as a sustainable ecotourism site. This study aims to analyze the potential of Amanah Borneo Park in the context of ecotourism and identify the challenges faced in realizing sustainable tourism in this area. The research employs a qualitative method with a descriptive approach, where data is collected through field observations, interviews with management, and related literature studies. The findings indicate that Amanah Borneo Park has significant potential in environmental, social, and economic aspects. However, several key challenges exist, such as limited infrastructure, low visitor awareness of ecotourism, and suboptimal promotion of the destination. Better management, the enhancement of eco-friendly facilities, and broader promotion can help increase the attractiveness and sustainability of this park as an ecotourism destination. The study concludes that with improvements in various aspects, Amanah Borneo Park can serve as a model for sustainable ecotourism in South Kalimantan. Keywords: Ecotourism, Sustainability, Amanah Borneo Park.